Apoptosis and oxidative stress as relevant mechanisms of antitumor activity and genotoxicity of ZnO-NPs alone and in combination with N-acetyl cysteine in tumor-bearing mice - El-Shorbagy HM; Eissa SM; Sabet S; El-Ghor AA (International Journal of Nanomedicine, 2019)
Haidan M El-Shorbagy, Shaymaa M Eissa, Salwa Sabet, Akmal A El-GhorDepartment of Zoology, Faculty of Science, Cairo University, Giza, EgyptBackground: Several in vitro studies have revealed that zinc oxide nanoparticles (ZnO-NPs) were able to target cancerous cells selectively with minimal damage to healthy cells.Purpose: In the current study, we aimed to evaluate the antitumor activity of ZnO-NPs in Ehrlich solid carcinoma (ESC) bearing mice by measuring their effect on the expression levels of P53, Bax and Bcl2 genes as indicators of apoptotic induction in tumor tissues. Also, we assessed the potential ameliorative or potentiation effect of 100 mg/kg N-acetyl cysteine (NAC) in combination with ZnO-NPs.Materials and methods: ESC bearing mice were gavaged with three different doses of ZnO-NPs (50, 300 and 500 mg/kg body weight) alone or in combination with NAC for seven consecutive days. In addition to measuring the tumor size, pathological changes, zinc content, oxidative stress biomarkers and DNA damage in ESC, normal muscle, liver and kidney tissues were assessed.Results: Data revealed a significant reduction in tumor size with a significant increase in p53 and Bax and decrease in Bcl2 expression levels in the tissues of ZnO-NPs treated ESC bearing mice. Moreover, a significant elevation of MDA accompanied with a significant reduction of CAT and GST. Also, a marked increase in all comet assay parameters was detected in ZnO-NPs treated groups. On the other hand, the combined treatment with ZnO-NPs and NAC significantly reduced reactive oxygen species production and DNA damage in liver and kidney tissues in all ZnO-NPs treated groups.Conclusion: ZnO-NPs exhibited a promising anticancer efficacy in ESC, this could serve as a foundation for developing new cancer therapeutics. Meanwhile, the combined treatment with ZnO-NPs and NAC could act as a protective method for the healthy normal tissue against ZnO-NPs toxicity, without affecting its antitumor activity.Keywords: ZnO-NPs, antitumor, Ehrlich solid carcinoma, N-acetyl cysteine, oxidative stress, DNA damage